2023
DOI: 10.1111/ctr.15187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes in vaccinated versus unvaccinated COVID‐19 kidney transplant recipients, a single center retrospective study—Is the taboo justified?

Priyamvada Singh,
Lauren Von Stein,
Melissa McGowan
et al.

Abstract: IntroductionWe assessed differences in the post‐transplant outcomes between COVID‐19 vaccinated and unvaccinated Kidney transplant (KTx) recipients.MethodsWe conducted a retrospective, single‐center study of 400 KTx from 2/1/2021 to 4/30/2022 with 6–21 months follow‐up. Primary outcomes included differences in the incidence of post‐transplant COVID‐19, ICU admission for COVID‐19, death, and graft failure between the two groups. Secondary outcomes were inpatient floor admission, outpatient‐management, length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…One study of 2500 KTRs found that the number of SARS-CoV-2 vaccination doses was inversely correlated with mortality, hospitalization, ICU admission, and acute kidney injury (AKI)[ 5 ]. On the other hand, a single-center study of 400 KTRs found no statistically significant differences between unvaccinated and vaccinated KTRs in terms of hospitalization (outpatient, general floor, ICU), length of stay, death, and graft failure[ 6 ]. It is important to note that in the study which noted a significant influence in vaccination on outcomes that it analyzed results according to the different SARS-CoV-2 variants, namely pre and post Omicron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of 2500 KTRs found that the number of SARS-CoV-2 vaccination doses was inversely correlated with mortality, hospitalization, ICU admission, and acute kidney injury (AKI)[ 5 ]. On the other hand, a single-center study of 400 KTRs found no statistically significant differences between unvaccinated and vaccinated KTRs in terms of hospitalization (outpatient, general floor, ICU), length of stay, death, and graft failure[ 6 ]. It is important to note that in the study which noted a significant influence in vaccination on outcomes that it analyzed results according to the different SARS-CoV-2 variants, namely pre and post Omicron.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center cohort study of 2500 KTRs found that vaccinated patients had improved outcomes concerning mortality, hospitalization, and intensive care unit (ICU) admission[ 5 ]. In another single-center study of 400 KTRs that compared unvaccinated and vaccinated recipients, there were no significant differences in the rates of ICU admission, length of hospital stay, death, or graft failure, although the incidence of SARS-CoV-2 infection was higher in the unvaccinated group[ 6 ]. Another study found that the severity of COVID-19 disease necessitating the hospitalization of KTRs was predominantly influenced by comorbid conditions and baseline kidney function [baseline estimated glomerular filtration rate (eGFR)]; however, they found that when adjusted for comorbidity and renal function, they found no statistically significant differences in mortality, ICU admission, and length of stay between adults hospitalized for COVID-19 who had undergone kidney transplant and non-transplanted counterparts[ 7 ].…”
Section: Introductionmentioning
confidence: 99%